2012
DOI: 10.4028/www.scientific.net/amr.554-556.985
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bioactive Ingredients in Five Pumpkin Seeds Cultivars

Abstract: Pumpkin is a widely cultivated vegetable used for human consumption and traditional medicine this investigation will provide much more information for the further exploration of pumpkin seeds. In the present study, the contents of total phenolics, phytosterols, squalene, α-tocopherol, polysaccharides and γ-aminobutyric acid (GABA) from the five types of pumpkin seeds cultivars were determined by established methods. The total phenolics contents of the pumpkin seeds ranged from 0.96 to 2.52 mg/g, total phytoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Camelina cake is rich in polyphenols (approximately 666 ± 40 mg CA/100 g for crude extract and 866 ± 20 mg CA/100 g for purified extract), and has high DPPH scavenging activity (9.4 ± 0.5 μg/ml for crude extract and 22.8 ± 0.1 μg/ml for purified extract) (Terpinc, Polak, Makuc, Ulrih, & Abramovič, ). Pumpkin seeds are a rich source of vitamins, minerals, and bioactive compounds like phytosterols, phenolic substances, squalene, and γ‐aminobutanoic acid (Qi, Yang, Wang, Xu, & Qu, ). Defatted pumpkin cake has more phenolic acids than pumpkin seeds (Peričin, Krimer, Trivić, & Radulović, ).…”
Section: Introductionmentioning
confidence: 99%
“…Camelina cake is rich in polyphenols (approximately 666 ± 40 mg CA/100 g for crude extract and 866 ± 20 mg CA/100 g for purified extract), and has high DPPH scavenging activity (9.4 ± 0.5 μg/ml for crude extract and 22.8 ± 0.1 μg/ml for purified extract) (Terpinc, Polak, Makuc, Ulrih, & Abramovič, ). Pumpkin seeds are a rich source of vitamins, minerals, and bioactive compounds like phytosterols, phenolic substances, squalene, and γ‐aminobutanoic acid (Qi, Yang, Wang, Xu, & Qu, ). Defatted pumpkin cake has more phenolic acids than pumpkin seeds (Peričin, Krimer, Trivić, & Radulović, ).…”
Section: Introductionmentioning
confidence: 99%
“…The squalene concentration was reported as 0.92 to 1.29 mg/g, whereas α-tocopherol was ranging from 83.09 to 98.57 μg/g. The results of the study also indicated the presence of a significant amount of γ-amino butyric acid (GABA) which was noted as 3.71-15.53 mg/100 g (Qi et al 2012). Phytosterol composition of pumpkin seeds is provided in Table 19.7.…”
Section: Phytonutrients/phenolicsmentioning
confidence: 92%
“…The contents of squalene in pumpkin seed oil in this study were higher than that previous report. Previous researchers have reported that the contents of squalene in pumpkin seed oil were in the range of 920 mg/kg to 1290 mg/kg 29 . This is probably related to the region and climate.…”
Section: Phytosterol and Squalencementioning
confidence: 99%